Clinical outcomes following pharyngolaryngectomy reconstruction: a 20-year single-centre study. Issue 11 (10th November 2022) - Layton, T; Thomas, R; Harris, C; Holmes, S; Fraser, L; Silva, P; Winter, S C
Abstract: Background: Advanced malignant neoplasms of the larynx and hypopharynx pose many therapeutic challenges. Total pharyngolaryngectomy and total laryngectomy provide an opportunity to cure these tumours but are associated with significant morbidity. Reconstruction of the pharyngeal defect following total pharyngolaryngectomy demands careful consideration and remains an area of debate within surgical discussions. Methods: This paper describes a systemic analysis of pharyngeal reconstruction following total pharyngolaryngectomy and total laryngectomy, leveraging data collected over a 20-year period at a large tertiary referral centre. Results: Analysing 155 patients, the results show that circumferential pharyngeal defects and prior radiotherapy have a significant impact on surgical complications. In addition, free tissue transfer in larger pharyngeal defects showed lower rates of post-operative anastomosis leak and stricture. Conclusion: Pharyngeal resection carries a substantial risk of post-operative complications, and free tissue transfer appears to be an effective means of reconstruction for circumferential defects.